Come again - Powell, Nate 1978- (Top Shelf Productions, 2018)
"A lover's dream becomes a parent's nightmare in the astonishing new graphic novel from Nate Powell. As the sun sets on the 1970s, the spirit of the Love Generation still lingers in one "intentional community" high in the Ozarks. But what's missing? Under impossibly close scrutiny, two families wrestle with long-repressed secrets... while deep within those Arkansas hills, something monstrous stirs, ready to feast on village whispers. In his triumphant return to solo cartooning, #1 New York Times bestseller Nate Powell presents a haunting tale of intimacy, guilt, and collective amnesia."--Publisher's website
Keywords: Geschichte 1970; Amnesie; Gemeinde; Geheimhaltung; Arkansas-River-Gebiet; Comic